Simple Nutritional Screening Tool (SNST) Has Good Validity to Identify Risk of Malnutrition on Hospitalized Elderly Patients - Mayasari, Meike; Susetyowati; Lestariana, Wiryatun (Pakistan Journal of Nutrition, 2014)
High prevalence of malnutrition related to adverse outcomes in elderly patients. A simple and inexpensive nutritional screening tool is required to detect malnutrition on the elderly in order to give a suitable intervention as early as possible. Mini Nutritional Assessment-Short Form (MNA-SF) is a screening tool developed specifically for elderly patient, however, it still requires anthropometric measurement and mathematic calculation. The new nutritional screening tool, SNST is a very easy, inexpensive and does not require mathematical calculation and anthropometric measurement. However, the validity of SNST to identify elderly patients who are at risk from malnutrition has not been tested yet. The aim of this study was to analyze the validity screening tool SNST compared with MNA-SF against anthropometry and biochemical of elderly patients in Dr. Sardjito Hospital. A cross sectional study was conducted to 268 elderly who were inpatient in RS Sardjito to test the validity of SNST compared with MNA-SF. Patients with mental disorders and oedema or ascites were excluded. BMI and MUAC data were obtained from direct measurements, whereas biochemical data such as albumin, haemoglobin and TLC obtained from patient’s medical record. SNST screening tool had sensitivity 88.3%, specificity 95.2%, positive predictive value 98.4%, negative predictive value 77.1% and area under ROC curve 0.918. SNST was also as good as MNA-SF in distinguishing elderly patients at risk and not at risk of malnutrition. Subjects who were at risk for malnutrition according SNST screening tool had significantly lower values of BMI, MUAC, albumin, hemoglobin and TLC than subjects who were not at risk for malnutrition (p<0.001). SNST screening tool has good validity to identify risk of malnutrition on hospitalized elderly patients.